2020
DOI: 10.3390/insects11090553
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Assemblages of Spiders in Mediterranean Pear Orchards and the Effect of Intensity of Spraying

Abstract: Spiders are key predatory arthropods that are negatively affected by spraying pesticides in orchards. The aim of this research was to determine the structure of the community of spiders in pear orchards and the impact of the intensity of spraying. The study was carried out over three years in four pear orchards in southern Spain; two of them were conducted by ourselves with no or low-intensity spraying of insecticides, and two under the criteria of technicians (conventional). Spiders were sampled on pear trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
(121 reference statements)
1
8
0
Order By: Relevance
“…2,20 The control of psyllids in this region is based mainly on the use of insecticides. 2,21,24 The present research, carried out in the southwestern Mediterranean area, demonstrated that the intensification in the use of insecticides indeed produced a reduction in the populations of C. pyri and the incidence of russet. However, the abundance of psyllids and the russet impact depended on the ecological context and were much reduced in the presence of ants, as the most important predator of psyllids in this area.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…2,20 The control of psyllids in this region is based mainly on the use of insecticides. 2,21,24 The present research, carried out in the southwestern Mediterranean area, demonstrated that the intensification in the use of insecticides indeed produced a reduction in the populations of C. pyri and the incidence of russet. However, the abundance of psyllids and the russet impact depended on the ecological context and were much reduced in the presence of ants, as the most important predator of psyllids in this area.…”
Section: Discussionsupporting
confidence: 51%
“…Pear psyllids are currently one of the main pests of pear orchards in temperate Europe and the Mediterranean basin, and one of the principal problems occasioned by psyllid infestations is the devaluation of fruits due to russet 2,20 . The control of psyllids in this region is based mainly on the use of insecticides 2,21,24 . The present research, carried out in the southwestern Mediterranean area, demonstrated that the intensification in the use of insecticides indeed produced a reduction in the populations of C. pyri and the incidence of russet.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations